Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Makanan dan Minuman Menggunakan Aplikasi Gojek Fitur Gofood - Purnomo Ari Wibowo; Ditho Vernanda (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to determine the effect of psychological factors (X1), promotion (X2), personal (X3), and service quality (X4) on purchasing decisions (Y) using the Gojek application featuring Gofood in MagelangRegency. The research used in the preparation of this research is quantitative. The population in this study are users of the Gojek application with Gofood features, with a sample of 97. Data collection method with a questionnaire. The methods used validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, and the coefficient of determination. The results of the multiple regression study showed that there was a partial positive effect of Psychological Factors on Purchasing Decisions (tcount 4.221 > ttable 1.98609), then Promotional Factors on Purchasing Decisions (tcount 2.561 > ttable 1.98609), Personal Factors on Purchase Decisions (tcount 2.400 > ttabl 1.98609), and Service Quality Factors on Purchasing Decisions (tcount 4.481 > ttable 1.98609). The influence of the four research variables is very strong with a correlation value of Adjusted R^2 = 0.626.. The results of this study indicate that psychological, promotional, personal, and service quality factors simultaneously have a positive and significant effect on purchasing decisions using Gofood